PENGELOLAAN MODAL KERJA SEBAGAI UPAYA MENINGKATKAN NILAI PROFITABILITAS DAN TINGKAT LIKUIDITAS KOPERASI - Rizki Aprilia Dwi Susanti (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2020)
This study aims to determine the management of working capital because it is very important for cooperatives in carrying out its operations to improve the profitability of cooperatives and can also maintain the level of cooperative liquidity. This type of research is qualitative descriptive with a quantitative approach. The results of this study showed under the working capital of Indonesian officials of Universitas Brawijaya Malang derived from members and capital of their own. The profitability of cooperatives in three years was increased in this case Due to the rise of assets from the net profit after tax while the liquidity is fluctuating due to the reduced cooperative cash used to fulfill a short-term obligation that results in declining liabilities The short-term cooperative in three years was in 2016 until 2018.